Analisis Penerapan Jalan Satu Arah di Ruas Jalan Raya Leles-Jalan Lingkar Leles - Anggie Rahman Hakim; Ida Farida (Institut Teknologi Garut, 2022)
This study aims to determine the causes of congestion that often occurs on Jalan Raya Leles during rush hours and determine the impact of implementing one-way roads on performance on Jalan Raya Leles during rush hours. This analysis was carried out by analyzing the existing road conditions as well as the one-way road conditions using the PTV software. Vissim. The cause of congestion on Jalan Raya Leles on existing road conditions is due to an increase in vehicle volume, namely 433 vehicles/minute or 3,468 vehicles/hour which causes a decrease in speed, namely 15.11 km/minute and an increase in density, namely 28.68 vehicles/minute. The implementation of one-way roads on the Leles Highway and Leles Ring Road sections in both scenarios results in an increase in vehicle speed and a decrease in vehicle density on the existing road. In scenario 1, the average vehicle speed is 45.70 veh/min and the vehicle density is 9.69 veh/km and the vehicle volume is 441 veh/min with an average confidence level of the modeling results using PTV software. Vissim that is 98%. In scenario 2 the average vehicle speed is 44.55 veh/min and the vehicle density is 6.70 veh/km and the vehicle volume is 450 veh/min with an average confidence level of modeling results using PTV software. Vissim that is 96%. So the implementation of one-way roads on the Leles Highway and Leles Ring Road sections can reduce congestion during rush hours. It is necessary to arrange more effective vehicle flow patterns so that they do not have a significant impact on increasing vehicle traffic on Jalan Raya Leles. Implementing a one-way road by diverting traffic flow during rush hours from Bandung to the Leles Ring Road section with a composition of motorbikes, private cars, freight transport while public transport vehicles and buses continue to pass Jalan Raya Leles. Meanwhile, from the direction of Garut on Jalan Raya Leles with a composition of motorbikes, private cars, goods transport, public transport and buses still passing through Jalan Raya Leles.